First-year nest growth in the leaf-cutting ants Atta bisphaerica and Atta sexdens rubropilosa - Cardoso, S. R. S. [UNESP] (2014)
Most ants, as leaf cutting ants, construct nests underground to maintain environmental conditions favorable to the development of immature and adult individuals. But there was little works about this, especially doing comparison of nest growth among leaf-cutting ant species. Thus, we studied the growth of nests of the leaf-cutting ants Atta bisphaerica and Atta sexdens rubropilosa from nest foundation until the appearance of a second chamber. To this end, we verified the measurements of the chamber recently constructed by the queen and monitored its growth in the initial phase of nest development. The nests were marked immediately after nuptial flight, with 40 nests of each species being dug at 45, 90, 135, 180, and 225 days afterwards. As a result, it was found a first time statistical demonstration that an ellipsoid chamber shape was verified in both species in the initial chamber at 45 days, and that, after, these chamber became spherical. In general, chamber size increased and format change was found in both species. The depth of the first chamber was found to increase significantly only in A. bisphaerica; this result means that this chamber growths downside rather than upside. The occurrence of a second chamber was verified from six months after nest foundation, in both species. Our study contributes to knowledge of the colony development for up to 1 year, by performing comparison of two leaf-cutting ants species.